2021
DOI: 10.1159/000519991
|View full text |Cite
|
Sign up to set email alerts
|

EEG Contribution to the Diagnosis of Antibody-Negative Autoimmune Encephalitis: A Case Report

Abstract: Autoimmune encephalitis (AE) is a group of inflammatory brain diseases that are characterized by prominent neuropsychiatric symptoms. Early therapeutic intervention is important for AE. Therefore, without waiting for autoantibody test results, clinicians must consider the possibility of AE based solely on clinical symptoms and conventional test results. The case described herein is of antibody-negative encephalitis with abnormalities shown only by EEG, which contributed to the diagnosis and treatment. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…5,6 The diagnostic criteria by Graus et al 4 showed that the absence of antibodies did not exclude AE, but the inclusion criteria for antibody-negative AE varied widely among available studies. [7][8][9] Recognition of antibody-negative AE patients is crucial as with prompt diagnosis and early administration of immunotherapy the majority have favorable outcomes. 4,10 According to data from Olmstead County published in 2015, the estimated prevalence was 6.5 per 100,000 persons ª 2024 The Authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The diagnostic criteria by Graus et al 4 showed that the absence of antibodies did not exclude AE, but the inclusion criteria for antibody-negative AE varied widely among available studies. [7][8][9] Recognition of antibody-negative AE patients is crucial as with prompt diagnosis and early administration of immunotherapy the majority have favorable outcomes. 4,10 According to data from Olmstead County published in 2015, the estimated prevalence was 6.5 per 100,000 persons ª 2024 The Authors.…”
Section: Introductionmentioning
confidence: 99%
“… 4 showed that the absence of antibodies did not exclude AE, but the inclusion criteria for antibody‐negative AE varied widely among available studies. 7 , 8 , 9 Recognition of antibody‐negative AE patients is crucial as with prompt diagnosis and early administration of immunotherapy the majority have favorable outcomes. 4 , 10…”
Section: Introductionmentioning
confidence: 99%